Historical Remarks about the Nature of the Diseases Invalidating Marriage Contract in Shiite Jurisprudence - Tavallaei, Ali (مجله علمی - پژوهشی فقه پزشکی, 2012)
Validity or invalidity of the marriage of a diseased man and the status of the marriage portion and inheritance of his wife is one of the issues disputed over between Madani and Iraqi Jurisprudents in second century. In Traditions narrated from Imams (A.S) marriage contract concluded in case of disease with having any sexual intercourse is a circumstantial evidence of the patient’s intent to damage the heirs and would be null and the wife would be entitled to no marriage portion and inheritance. Although there is no dispute over the nullity of marriage in the aforesaid case, determining the nature and type of disease is an issue that should be discussed in details. Expressions like “عند الموت” and “مات فی مرضه” are used In Quran and Sunna has led Jurisprudents to infer on the nature of this term and to name it the "death disease" and have disagreed about the explanation of its nature. Some jurisprudents have argued that the meaning of this disease is a disease that in medical terms would result in death certainly or frequently: A frightening disease. Even in jurisprudential texts, some samples of this disease have been determined according to the ancient medicine. By a historical view, different opinions and forms of disease have been explained in this paper. In light of historical view, this perspective may be supported that a disease invalidating the marriage contract is an incurable disease that from the medical point of view would results in death within a short time Disease, Marriage, Shiite Jurisprudence, Death, sexual Intercourse